2012
DOI: 10.1124/dmd.112.044883
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Polymorphic Allele of Human Arylacetamide Deacetylase Leads to Decreased Enzyme Activity

Abstract: ABSTRACT:Human arylacetamide deacetylase (AADAC) is responsible for the hydrolysis of clinically used drugs such as flutamide, phenacetin, and rifamycins. Our recent studies suggested that human AADAC is a relevant enzyme pharmacologically and toxicologically. To date, the genetic polymorphisms that affect enzyme activity in AADAC have been unknown. In this study, we found single-nucleotide polymorphisms in the human AADAC gene in a liver sample that showed remarkably low flutamide hydrolase activity. Among th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(48 citation statements)
references
References 28 publications
2
45
0
1
Order By: Relevance
“…Recombinant human AADAC, CES1, and CES2 expressed in baculovirus-infected insect cells were prepared as previously described Watanabe et al, 2010). The homogenates of COS7 cells, fibroblast-like cell line from monkey kidney tissue, expressing AADAC.1, AADAC.2, and AADAC.3 were prepared as in our previous study (Shimizu et al, 2012). All other chemicals used in this study were of analytical or the highest quality commercially available.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recombinant human AADAC, CES1, and CES2 expressed in baculovirus-infected insect cells were prepared as previously described Watanabe et al, 2010). The homogenates of COS7 cells, fibroblast-like cell line from monkey kidney tissue, expressing AADAC.1, AADAC.2, and AADAC.3 were prepared as in our previous study (Shimizu et al, 2012). All other chemicals used in this study were of analytical or the highest quality commercially available.…”
Section: Methodsmentioning
confidence: 99%
“…We previously found polymorphic alleles of the human AADAC gene (Shimizu et al, 2012): AADAC*2 and AADAC*3. The AADAC proteins encoded by AADAC*2 and AADAC*3 are AADAC.2 and AADAC.3.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…4A). The results of a later study found that this sample has a polymorphic allele of AADAC gene, which causes the decreased enzyme activity (Shimizu et al, 2012).…”
Section: Resultsmentioning
confidence: 76%
“…Se ha reportado que es una enzima relacionada al metabolismo de RIF, miembro de la superfamilia de serina esterasa, la cual se expresa en el hígado y en el tracto gastrointestinal (36) . Uno de los polimorfismos que ha sido reportado por afectar la actividad de esta enzima es AADAC*3: 14008T>C. Esta enzima está siendo considerada y analizada en un estudio actual del Instituto Nacional de Salud en pacientes con tuberculosis, trabajo en el que reportarán los genotipos presentes en nuestra población.…”
Section: Aadacunclassified